Economic anatomy, element abundance and optimality: A new way of examining hunters’ bone transportation choices - Outram, Alan K (Archaeopress, 2001)
© Individual authors, 2001 The importance of studying skeletal part abundance, with respect to economic anatomy, is outlined. The current methodology in this field is discussed. A new method for examining archaeological skeletal part abundance, with respect to bone transportation models, is described. This method scrutinises the difference between observed abundance and economically expected abundance according to food utility. This new method is closely linked to optimal foraging theory. The application of optimal foraging theory to the question of bone transportation by hunters is discussed. The use of the new methodology is illustrated by application to two ethnographic examples; the Inuit sites of Anavik and Anaktiqtauk (Binford 1978). Issues related to the application of such a methodology to archaeological assemblage are discussed.